New ATRP initiator for synthesis of cyclic carbonate-terminated poly(methyl methacrylate) - Palaskar, Dnyaneshwar V.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2010)
A new ATRP initiator, viz, 2-oxo-1,3-dioxolan-4-yl-(methyl-2-bromo-2-methylpropanoate) (ODMBMP) was synthesized by the reaction of commercially available glycerol carbonate with 2-bromoisobutyrylbromide and was used to carry out ATRP reactions of methyl methacrylate (MMA) in the presence of copper chloride/N,N',N',N''N''-pentamethyldiethylenetriamine to afford low molecular weight (M(n)(GPC) = 1750-7550) cyclic carbonate-terminated poly(methyl methacrylate)s with relatively narrow molecular weight distribution (M(w)/M(n) = 1.16-1.30). Poly(methyl methacrylate)s having higher molecular weight (M(n)(GPC) = 18,250 and 44,130) could also be synthesized using ODMBMP as the ATRP initiator. The kinetic studies of bulk ATRP of MMA showed a linear relationships between both In[M](o)/[M(t)] vs time and molecular weight vs conversion indicating controlled/living polymerization. The presence of cyclic carbonate functionality in poly(methyl methacrylate)s was confirmed by FUR. (1)H NMR, and (13)C NMR spectroscopy. The reactivity of cyclic carbonate group was demonstrated by a model reaction using n-propyl amine and the results showed quantitative conversion to hydroxyl urethane group. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Atom transfer radical polymerization (ATRP); cyclic carbonate; functional polymers; poly(methyl methacrylate)

Synthesis and characterization of aromatic polyazomethines bearing pendant pentadecyl chains - More, Arvind S.; Sane, Prakash S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
Aromatic diamine monomer viz., 4-(4'-aminophenoxy)-2-pentadecylbenzenamine containing pendant pentadecyl chain was synthesized starting from cashew nut shell liquid - a renewable resource material and was characterized by FTIR, (1)H and (13)C NMR spectroscopy. A series of new (co) polyazomethines containing pendant pentadecyl chains and flexibilizing ether linkages was synthesized by polycondensation of 4-(4'-aminophenoxy)-2-pentadecyl benzenamine with commercially available aromatic dialdehydes viz., terephthaldehyde (TPA), isophthaldehyde (IPA) and varying mixture of TPA and IPA. Inherent viscosities and number average molecular weights of (co) polyazomethines were in the range 0.50-0.70 dL/g and 10,490-40-800 (GPC, polystyrene standard), respectively indicating formation of medium to reasonably high molecular weight polymers. (Co) polyazomethines containing pendant pentadecyl chains were found to be soluble in common organic solvents such as chloroform, dichloromethane, tetrahydrofuran, pyridine, m-cresol and could be cast into transparent and stretchable films from their solution in chloroform. (Co) polyazomethines were essentially amorphous in nature and the formation of loosely-developed layered structure was observed arising from the packing of pendant pentadecyl chains. Polyazomethines exhibited glass transition temperatures (T(g)) in the range 21-48 degrees C. The observed depression of glass transition temperature could be ascribed to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% wt loss (T(10)), determined from TGA in nitrogen atmosphere of polyazomethines were in the range 434-441 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; CNSL; pentadecyl; polyazomethines; renewable; Side-chain; solubility

Synthesis of bis-allyloxy functionalized polystyrene and poly (methyl methacrylate) macromonomers using a new ATRP initiator - Sane, Prakash S.; Palaskar, Dnyaneshwar V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2011)
A new bis-allyloxy functionalized ATRP initiator, viz, 4,4-bis (4-(allyloxy) phenyl) penty1-2-bromo-2-methylpropanoate was synthesized starting from commercially available 4,4-bis (4-hydroxyphenyl) pentanoic acid. Atom transfer radical polymerization of styrene in bulk and that of methyl methacrylate in anisole using CuBr/N,N,N',N',N `'-pentamethyldiethyl-enetriamine system was carried out. The kinetic study of styrene polymerization showed controlled polymerization behavior. Bis-allyloxy functionalized well-defined polystyrene (M(n)(GPC): 13,600-28,250, PDI: 1.07-1.09) and poly (methyl methacrylate) (M(n)(GPC): 10,100-18,450, PDI: 1.23-1.34) macromonomers were obtained. The presence of allyloxy functionality was confirmed by (1)H NMR spectroscopy. The reactivity of allyloxy functionality was demonstrated by carrying out organic reactions such as addition of bromine and hydrosilylation on polystyrene macromonomer. Polystyrene macromonomer with bis-allyloxy functionality was transformed into bis-epoxy functionalized polystyrene macromonomer using 3-chloroperoxybenzoic acid. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Allyloxy end-functional polymer; Atom transfer radical polymerization (ATRP); Macromonomers; Poly (methyl methacrylate); Polystyrene

Aromatic aldehyde functionalized polycaprolactone and polystyrene macromonomers: synthesis, characterization and aldehyde-aminooxy click reaction - Sane, Prakash S.; Tawade, Bhausaheb V.; Palaskar, Dnyaneshwar V.; Menon, Shamal K.; Wadgaonkar, Prakash P. (Reactive & Functional Polymers, 2012)
New bis-aldehyde functionalized initiators, viz, 4,4'-(4,4'-(5-hydroxypentane-2,2-diyl)bis(4,1-phenylene))bis(oxy)dibenza ldehyde (1) and 4,4'-bis(4-(4-(formylphenoxy) phenyl) pentyl 2-bromopropanoate (2) were synthesized starting from commercially available 4,4'-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of E-caprolactone and atom transfer radical polymerization of styrene. Well-defined polycaprolactone macromonomers (M-n(GPC): 2600-19400, PDI: 1.37-1.47) and polystyrene macromonomers (M-n(GPC): 2800-28200, PDI: 1.11-1.16) with bis-aldehyde functionality were synthesized. The kinetic study of styrene polymerization showed controlled polymerization behaviour. The presence of aldehyde functionality in macromonomers was confirmed by H-1 NMR spectroscopy. The reactivity of aldehyde functionality was demonstrated by carrying out aldehyde-aminooxy click reaction of polycaprolactone macromonomer with O-(2-azidoethyl) hydroxylamine which proceeded in a quantitative manner without backbone degradation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aldehyde-terminated macromonomers; ATRP; Polycaprolactone; Polystyrene; ROP

Facile strategy for synthesis of ,-heterobifunctionalized poly (epsilon-caprolactones) and poly (methyl methacrylate)s containing ``clickable'' aldehyde and allyloxy functional groups using initiator approach - Sane, Prakash S.; Tawade, Bhausaheb V.; Parmar, Indravadan; Kumari, Savita; Nagane, Samadhan; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2013)
Two new initiators, namely, 4-(4-(2-(4-(allyloxy) phenyl)-5-hydroxypentane 2-yl) phenoxy)benzaldehyde and 4-(4-(allyloxy) phenyl)-4-(4-(4-formylphenoxy) phenyl) pentyl 2-bromo-2-methyl propanoate containing clickable hetero-functionalities namely aldehyde and allyloxy were synthesized starting from commercially available 4,4-bis(4-hydroxyphenyl) pentanoic acid. These initiators were utilized, respectively, for ring opening polymerization of epsilon-caprolactone and atom transfer radical polymerization of methyl methacrylate. Well-defined -aldehyde, -allyloxy heterobifunctionalized poly(epsilon-caprolactones) (Mn,GPC: 590029,000, PDI: 1.261.43) and poly(methyl methacrylate)s (Mn,GPC: 530028800, PDI: 1.191.25) were synthesized. The kinetic study of methyl methacrylate polymerization demonstrated controlled polymerization behavior. The presence of aldehyde and allyloxy functionality on polymers was confirmed by 1H NMR spectroscopy. Aldehyde-aminooxy and thiol-ene metal-free double click strategy was used to demonstrate reactivity of functional groups on polymers. (c) 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013, 51, 2091-2103
Keywords: atom transfer radical polymerization; Click chemistry; functional polymers; ring opening polymerization

Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties

Aromatic polyesters containing pendant azido groups: synthesis, characterization, chemical modification and thermal cross-linking - Nagane, Samadhan S.; Verma, Savita; Tawade, V, Bhausaheb; Sane, Prakash S.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (European Polymer Journal, 2019)
A partially bio-based bisphenol containing pendant azido group viz., 4,4'-(5-azidopentane-2,2-diyl) diphenol (AZBPA) was synthesized starting from 4,4'-bis (4-hydroxyphenyl) pentanoic acid. AZBPA was reacted with isophthaloyl chloride (IPC), terephthaloyl chloride (TPC) and a mixture of IPC/TPC (50:50 mol%) by phase transfer-catalyzed interfacial polycondensation route to obtain aromatic polyesters containing pendant azido groups. Copolyesters containing pendant azido groups were also synthesized by polycondensation of different molar proportions of AZBPA and commercially available 4,4'-(1-phenylethane-1,1-diyl) diphenol (BPA-AP) with IPC. Inherent viscosities and number average molecular weights of (co)polyesters were in the range 0.85-1.64 dL/g and 58,900-190,400, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these polyesters. X-Ray diffraction analysis showed that (co)polyesters were amorphous in nature. (Co)polyesters were characterized using FT-IR, H-1 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolyester containing pendant azido groups was carried out quantitatively using copper-catalyzed azide-alkyne cycloaddition (CuAAC) with two alkynes viz., phenyl acetylene (PA) and ethynyl-4-nitrobenzene (ENB). Additionally, (co)polyesters containing pendant azido groups were thermally cross-linked (170 degrees C/12 h) leading to the formation of network structures based on azide to nitrene decomposition and subsequent reactions on polyester backbone. The selected cross-linked polyesters were characterized by stress-strain measurements. The cross-linked polymers exhibited higher tensile strength and Young's modulus and lower % elongation at break compared to corresponding pristine polyesters containing pendant azido groups.
Keywords: Aromatic polyester; Chemical modification; Click chemistry; Pendant azido group; Thermal cross-linking